Radiation synthesis and characterization of starch-acrylic acid-nanohalloysite composite for the removal of Co(II) ions from aqueous solutions. (January 2023) - Elsharma, Emad M.; Abdelmonem, Islam M.; Emara, Amr M.
Abstract: In this study, gamma rays were used as an initiator to prepare starch-acrylic acid/nanohalloysite, P(Stc-AA/NHal) composite for the removal of Co(II) from aqueous solutions. The characteristic peaks of P(Stc-AA/NHal) composite was confirmed by Fourier transform infrared spectroscopic analysis (FTIR). The morphological structure was examined using a scanning electron microscope (SEM). Differential thermal analysis (DTA) and thermogravimetric analysis (TGA) were also used to characterize the composite and demonstrate its high thermal stability. Using a batch sorption technique and 60 Co as a radiotracer, the P(Stc-AA/NHal) composite was evaluated for Co(II) ions removal from aqueous solutions. The effect of pH, contact time, metal ion concentration, and temperature on Co(II) ions sorption were studied. The kinetic data of adsorption fit accurately with the pseudo-second-order adsorption model. Finally, the equilibrium adsorption results fitted the Langmuir isotherm model very well. The highest adsorption capacity measured was 103.6 mg g −1 Highlights: P(Stc-AA/NHal) composite was synthesized by gamma radiation. P(Stc-AA/NHal) composite was confirmed by FTIR, SEM, TGA and DTA. Cobalt radionuclides was removed with high capacity. The kinetic data of adsorption fit well with the pseudo-second-order adsorption model. The equilibrium adsorption results fitted the Langmuir isotherm model very well.